Effects of Si addition on the martensitic transformation, structural and thermodynamic aspects in Fe45−xMn30Cr10Co15Six high entropy alloys - Acciarri, M. D; la Roca, Paulo Matías; Guerrero Salazar, Lina Maria; Malamud, Florencia; Baruj, Alberto Leonardo; Sade Lichtmann, Marcos Leonel (Korean Institute of Metals and Materials, 2023)
Fil: Acciarri, M. D. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. University of Michigan; Estados Unidos